Ready for VR? Assessing VR competence and exploring the role of human abilities and characteristics - Oberdörfer, Sebastian; Heinisch, Melina; Mühling, Tobias; Schreiner, Verena; König, Sarah; Latoschik, Marc Erich (Frontiers in Virtual Reality, 2025)
The use of VR for educational purposes provides the opportunity for integrating VR applications into assessments or graded examinations. Interacting with a VR environment requires specific human abilities, thus suggesting the existence of a VR competence. With regard to the emerging field of VR-based examinations, this VR competence might influence a candidate’s final grade and hence should be taken into account. In this paper, we proposed and developed a VR competence assessment application. The application features eight individual challenges that are based on generic 3D interaction techniques. In a pilot study, we measured the performance of 18 users. By identifying significant correlations between VR competence score, previous VR experience and theoretically-grounded contributing human abilities and characteristics, we provide first evidence that our VR competence assessment is effective. In addition, we provide first data that a specific VR competence exists. Our analyses further revealed that mainly spatial ability but also immersive tendency correlated with VR competence scores. These insights not only allow educators and researchers to assess and potentially equalize the VR competence level of their subjects, but also help designers to provide effective tutorials for first-time VR users.